2003
DOI: 10.1590/s0100-204x2003000700003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mandarin citrus germplasm from Southern Brazil by morphological and molecular analyses

Abstract: -The objective of this work was to characterize mandarin (Citrus spp.) germplasm from Southern Brazil by morphological and molecular analyses. Thirty seven cultivars from 34 distinct mandarin varieties were evaluated by morphological and agronomic traits of leaves, flowers and fruits, and by microsatellite markers. The morphological and agronomic characteristics suggested that almost all varieties can be produced for commercial use, and some, as the Satsuma variety, are recommended for breeding programs. Poole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
18

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 9 publications
5
26
0
18
Order By: Relevance
“…On the other hand, the agronomic x molecular data showed were not significantly correlated (-0.02). Similar results were observed in other crops, e.g., oat (Moser and Lee 1994) and citrus (Koehler-Santos et al 2003).…”
Section: Resultssupporting
confidence: 88%
“…On the other hand, the agronomic x molecular data showed were not significantly correlated (-0.02). Similar results were observed in other crops, e.g., oat (Moser and Lee 1994) and citrus (Koehler-Santos et al 2003).…”
Section: Resultssupporting
confidence: 88%
“…It is interesting to note that the level of conservation of the microsatellite loci developed in our study has also been observed in studies on grapefruit and mandarin (Corazza-Nunes et al, 2002;Koehler-Santos et al, 2003), in work on the saturation of genetic maps (Cristofani et al, 2003) and in the multiple analyses of the loci of inter-specific progenies (Cristofani et al, 2001;Oliveira et al, 2002). For this reason it is important that the microsatellite markers developed by us are made available for studies involving the molecular characterization of different citrus species and hybrids, to which end we have fully listed them on the CAPTACSM website site (www.centrodecitricultura.br/SSR.htm).…”
Section: Discussionsupporting
confidence: 82%
“…Printed in Brazil www.sbg.org.br (Viruel and Hormaza, 2004). In Citrus and related genera, microsatellites have been employed for phylogenetic studies (Fang and Roose, 1997;Pang et al, 2003), assessment of genetic variability (Kijas et al, 1995;Corazza-Nunes et al, 2002;Koehler-Santos et al, 2003), identification of zygotic plants (Ruiz et al, 2000;Cristofani et al, 2001;Oliveira et al, 2002) and construction and integration of linkage maps (Kijas et al, 1997;Cristofani et al, 2003) but it is still difficult to identify intraspecific variability in some Citrus species.…”
Section: Introductionmentioning
confidence: 99%
“…Um total de 16 pares de primers foram utilizados, sendo seis pertencentes à série Ma, desenvolvida por Crouch et al (1998); cinco pares da série AGMI, desenvolvidos por Lagoda et al (1998); três da série MaOCEN, obtidos por Creste et al (2006); um primer (STMS 1), obtido por Kaemmer et al (1997), e um primer (Mb 1-100), descrito por Oriero et al (2006) (Tabela 2).…”
Section: Caracterização Molecular Via Microssatélites Ou Ssrunclassified